Untangling the Web of Influences on Dental Students' Participation in Interprofessional Education Programs. Issue 6 (1st June 2016) - Foster Page, Lyndie A.; Gray, Lesley; Gallagher, Peter; McKinlay, Eileen; Rich, Alison M.
Abstract : The aim of this study was to explore how dental students involved in an experiential interprofessional education (IPE) program in New Zealand made sense of engaging in this unfamiliar learning environment. Qualitative data gathered from students during group interviews were analyzed to better understand how they assessed the IPE experience. Interviews were audiorecorded and transcribed before analysis of students' comments was undertaken, using constant comparison analysis and taking an inductive approach to the initial coding. Once each of the investigators had gone through his or her own transcripts, they reviewed each other's coding and agreed‐upon categories before applying the 3‐P model of student learning. Over a three‐year period (2012–14), 16 focus groups were conducted with students from multiple health professions. In total, 24 dental students participated. Six categories of comments made in the focus groups were identified: expectations and realizations; not practicing; trade‐offs/losses; learning with, from, and about each other; becoming open to a different clinical experience; valuing dental students' participation in IPE; and learning about what dentists do. From these categories, three main themes emerged: becoming a dentist, negotiating IPE experience, and valuing dentistry. The 3‐P model highlighted the complexity of IPE, and the challenges suggested that dental students may need extra preparation prior to participating in IPE programs.